2014
DOI: 10.4995/wrs.2014.1351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of spirulina (Arthrospira platensis) and thyme (Thymus vulgaris) on apparent digestibility and productive performance of growing rabbits

Abstract: The aim of this study was to evaluate the effect of dietary supplementation with spirulina (Arthrospira platensis) or/and thyme (Thymus vulgaris) on total tract apparent digestibility of nutrients and the performance of growing rabbits. At weaning (5 wk of age) the rabbits were randomly allotted to 7 groups (42 rabbits/group, 3 rabbits/cage). Rabbits in the control group (C-C) received a control pelleted feed throughout the experiment (5-11 wk of age) without any supplementation (crude protein: 176 g CP/kg, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 22 publications
5
32
2
Order By: Relevance
“…Water and feed were available ad libitum and the temperature and photoperiod in the rabbitry were 15-18 °C and 16L:8D, respectively. Ingredients and chemical composition of the experimental diets are reported in this same issue by Gerencsér et al (2014).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Water and feed were available ad libitum and the temperature and photoperiod in the rabbitry were 15-18 °C and 16L:8D, respectively. Ingredients and chemical composition of the experimental diets are reported in this same issue by Gerencsér et al (2014).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The results presented in this article are part of a wider study that has involved productive performance, the health status and apparent digestibility of the diets (Gerencsér et al, 2014), microbial diversity in the caecum and caecal fermentation (Vàntus et al, 2012), the fatty acid profile of the meat and its oxidative status during retail display (Dal Bosco et al, 2013). To our knowledge, this is the first study that evaluates the synergic effect of spirulina and thyme on animal productive performance, health, and meat quality.…”
mentioning
confidence: 99%
“…Moreover, the experimental controlled rearing condition, which was characterized by lower stress levels than intensive rearing conditions, could have affected the final results. According to Gerencsér et al (2012), in a favourable environment where the rabbits have a high health status, no further increase in production can be achieved. (Castellini et al, 1998) and no statistical differences among groups are reported.…”
Section: Productive Performancementioning
confidence: 99%
“…Recently, the effects of spirulina supplementation on animal performance and quality of animal products have been examined in the diets of dairy cows (Simkus et al, 2007;Christaki et al, 2012), fattening lambs (EL-Sabagh et al, 2014), rabbits (Colla et al, 2008;Peiretti & Meineri, 2008;Gerencser et al, 2014), common carp (Abdulrahman & Hamad Ameed, 2014), pigs (Grinsteal et al, 2000), laying hens (Carrillo et al, 2008;Maries et al, 2012;Zahroojian et al, 2013) and broilers (Ross & Dominy, 1990;Toyomizu et al, 2001;Alvarenga et al, 2011;Bellof & Alarcon, 2013). Nevertheless, published data could not be found on the effects of dietary spirulina on chicken meat oxidative stability and fatty acid profile.…”
Section: Introductionmentioning
confidence: 99%